An Observational Study on Clinical Characteristics and Outcomes of COVID-19 Patients Urgently Hospitalised from COVID Assessment Centres in Seremban, Malaysia - MI, Nor Azila; A, Ahmad Baihaqi; A, Nur Aslizah; AR, Nur Haizumraimi; MAR, Nur Saadah (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: COVID-19 emerged as a major global health problem in late 2019. At present, Malaysia has recorded more than 2 million cases since its first case; detected in January 2020. This study describes the clinical characteristics and outcome of COVID-19 patients urgently hospitalised in Seremban district from its local COVID Assessment Centre (CAC). Methods. Clinical records of all confirmed COVID-19 cases admitted urgently from three designated CACs between July and September 2021 in Seremban district were retrieved. The demography and clinical characteristics were captured, and the COVID vaccination status and clinical outcomes of each case were obtained and descriptively analysed using SPSS version 22.0. Results. A total of 240 samples were analysed. About 54.6% were female and 45.4% were male. The median age was 51 years. Majority of the cases were Malay, followed by Indian and Chinese, which was 67.5%, 17.5% and 12.1% of all cases, respectively. The median day of the illness was day 5, and the vast majority (77.1%) of cases were COVID-19 category 4. Most (72.5%) cases have underlying medical illnesses. The average body mass index (BMI) among the cases was 29.9 kg/m2 whereby 40.4% of them were obese with a BMI of 30 kg/m2 and above. Breathlessness was the most reported symptom (39.2%), followed by cough (28.7%). About 25.3% of them did not report any symptoms. Of all the cases urgently hospitalised, the recorded fatality was 9.6%, whereby 91.3% of them were not completely vaccinated. Conclusion. The majority of these urgently hospitalised patients were admitted due to COVID-19 category 4 infection. Most of them already had underlying medical problems and nearly half were obese. Most of the patients admitted who ended with mortality did not complete their vaccination. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S40